Factorial Composition of a General Self-Efficacy Scale in Mexican University Students - Grabriel Gastelum Cuadras; Perla Jannet Jurado Garcia; Susana Ivonne Aguirre Vasquez; María de los Angeles Bibiano Mejia (European Scientific Journal, ESJ, 2016)
The present study aims to investigate whether the psychometric results proposed by (Sanjuan, Perez, & Bermúdez, 2000) for general selfefficacy scale replicate. The total sample was of 282 subjects; 142 women and 140 men, college students from the city of La Paz Baja California Sur Mexico, with an mean age of 20.3 years (SD = 1.6) for women and 20.9 years (SD = 1.6) for men. The factorial structure of the questionnaire was analyzed by confirmatory factor analysis. The analysis shows a feasible and appropriate factor structure. The structure of a one factor, based on statistical and substantive criteria, has shown adequate fit indicators of reliability and validity. In addition, the factor obtained a Cronbach´s alpha coefficient of .914. Future research should replicate these findings in larger samples.